2015
DOI: 10.1039/c4ra14039g
|View full text |Cite
|
Sign up to set email alerts
|

A novel strategy to enhance ultraviolet light driven photocatalysis from graphene quantum dots infilled TiO2 nanotube arrays

Abstract: a Herein, a novel strategy has been proposed to fabricate graphene quantum dots (GQDs) infilled titanium dioxide (TiO 2 ) nanotube arrays (NTAs) hybrid structure for dye degradation of methylene blue (MB) under UV light (365 nm) irradiation. GQDs are infilled inside the TiO 2 NTAs (via anodic oxidation of a Ti sheet) through an impregnation method. Moreover, the morphology of the TiO 2 NTAs is well maintained after filling the GQDs inside, which is favorable for mass transfer. The peak intensity of photolumine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…For example, Gupta et al. reported a photocatalyst based on efficient modification of TiO 2 nanotube arrays with GQDs through an impregnation method, and the obtained photocatalyst could efficiently photo‐decompose methylene blue in aqueous solution under ultraviolet light irradiation . Zhuo et al.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…For example, Gupta et al. reported a photocatalyst based on efficient modification of TiO 2 nanotube arrays with GQDs through an impregnation method, and the obtained photocatalyst could efficiently photo‐decompose methylene blue in aqueous solution under ultraviolet light irradiation . Zhuo et al.…”
Section: Introductionsupporting
confidence: 76%
“…For example, Gupta et al reported ap hotocatalyst based on efficient modification of TiO 2 nanotube arrays with GQDs througha ni mpregnation method, and the obtainedp hotocatalyst could efficiently photo-decompose methylene blue in aqueous solution under ultraviolet light irradiation. [47] Zhuo et al developed the composite of GQDs/TiO 2 nanoparticles by an ultrasonic way for degradation of methylene blue. [48] Qu et al prepared GQDs with up-conversion properties and the heterojunction of GQDs/TiO 2 nanotubes by the hydrothermalm ethod.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GQDs can be prepared from cheap and accessible precursors [31,32]. Therefore, GQDs have already been used to form composites with inorganic semiconductors, which exhibited photocatalytic activity [33,34]. Nevertheless, to the best of our knowledge nickel and aluminum oxides or mixed Ni/Al oxides have not been examined in that context.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, many encouraging achievements have been made in the research of graphene-based semiconductor photocatalysts. [3][4][5] Graphene is a two-dimensional (2D) material composed of sp 2 -bonded carbon atoms that are linked in hexagonal shapes, with each carbon atom covalently bonded to three other carbon atoms. [6] Graphene has a large theoretical specific surface area, superior mobility of charge carriers, and high thermal/chemical stability.…”
Section: Introductionmentioning
confidence: 99%